Automated Diseased Lung Volume Percentage Calculation in Quantitative CT Evaluation of Chronic Obstructive Pulmonary Disease and Idiopathic Pulmonary Fibrosis. Issue 4 (July 2021) - Kitaguchi, Yoshiaki; Fujimoto, Keisaku; Droma, Yunden; Yasuo, Masanori; Wada, Yosuke; Ueno, Fumika; Kinjo, Takumi; Kawakami, Satoshi; Fukushima, Kiyoyasu; Hanaoka, Masayuki
Abstract : Objective: Several software-based quantitative computed tomography (CT) analysis methods have been developed for assessing emphysema and interstitial lung disease. Although the texture classification method appeared to be more successful than the other methods, the software programs are not commercially available, to our knowledge. Therefore, this study aimed to investigate the usefulness of a commercially available software program for quantitative CT analyses. Methods: This prospective cohort study included 80 patients with chronic obstructive pulmonary disease (COPD) or idiopathic pulmonary fibrosis (IPF). Results: The percentage of low attenuation volume and high attenuation volume had high sensitivity and high specificity for detecting emphysema and pulmonary fibrosis, respectively. The percentage of diseased lung volume (DLV%) was significantly correlated with the lung diffusion capacity for carbon monoxide in all patients with COPD and IPF patients. Conclusions: The quantitative CT analysis may improve the precision of the assessment of DLV%, which itself could be a useful tool in predicting lung diffusion capacity in patients with the clinical diagnosis of COPD or IPF.